Bacterial Biofilms 2020
DOI: 10.5772/intechopen.89362
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota from the Stomatology Perspective

Abstract: Besides the properties typical of body cavities, the oral cavity exhibits many differentiating features that allow it to occupy position of an autonomous functional and biological unit, a characteristic ecosystem. An appropriate homeostasis of oral biocenosis and balanced conditions for microorganisms concerning proportions of physiological and pathogenic or potentially pathogenic microbiota play an important role with regard to the oral cavity health and eventually the overall health of an individual. The ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The antibacterial effectiveness of honey has been demonstrated in many studies [23][24][25][26][27]. The exact mechanism is not yet clear, although it is commonly attributed to (i) the high sugar content, which induces high osmolarity and inhibits bacterial growth, (ii) oxygen peroxide, which is produced by the activation of glucose oxidase and (iii) the low and acidic pH (usually 3.2-4.5) [6,7,22,26]. However, there is more to be said on the matter.…”
Section: The Antibacterial Effectiveness Of Honeymentioning
confidence: 99%
See 2 more Smart Citations
“…The antibacterial effectiveness of honey has been demonstrated in many studies [23][24][25][26][27]. The exact mechanism is not yet clear, although it is commonly attributed to (i) the high sugar content, which induces high osmolarity and inhibits bacterial growth, (ii) oxygen peroxide, which is produced by the activation of glucose oxidase and (iii) the low and acidic pH (usually 3.2-4.5) [6,7,22,26]. However, there is more to be said on the matter.…”
Section: The Antibacterial Effectiveness Of Honeymentioning
confidence: 99%
“…Various pathogens, such as Streptococcus mutans exhibit their action causing serious health and oral health problems such as dental caries, while Staphylococcus aureus is found in periodontal pockets and other inflammations of the oral mucosa finally resulting in loss of 2 of 25 teeth [7,8]. In addition, it has been clinically demonstrated that bacteria from oral cavity are transported to other locations in the body causing infections such as inflammatory bowel disease (IBS) or participating in the pathogenesis of diseases such as the cirrhotic liver or Alzheimer's disease, diabetes melitus, adverse pregnancy outcomes, obesity, and polycystic ovary syndrome [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral cavity, which has specific individualized conditions, is characterized by its environment having a wide variety of pH, bacterial load, and/or temperature variation [ 7 ]. Temperature and pH are two significant factors that affect the electrochemical behavior of dental materials [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of Dentoalveolar abscess is polymicrobial in nature, comprising of various facultative anaerobes, such as the viridans group streptococci and the Streptococcus anginosus group, and strict anaerobes, especially anaerobic cocci, Prevotella and Fusobacterium species [2] . The presentation of bacterial infection of dental origin is constantly changing and is a measurable reflection of modern evolution of oral flora [3,4] . It has been suggested that, for the pathogenicity of strictly anaerobic gram-positive cocci the possession of a capsule (consisting of two, well characterised polysaccharides) a very important virulence factor of these bacteria [5] .…”
Section: Introductionmentioning
confidence: 99%